Green solvents for the selective extraction of bioactive compounds from by-products of the coffee production chain - da Silva, Mariana Rodrigues [UNESP]; Jelley, Rebecca E.; Carneiro, Renato Lajarim; Fedrizzi, Bruno; Weber, Cameron C.; Funari, Cristiano Soleo [UNESP] (Elsevier, 2023)
Approximately 15–20 million tonnes of by-products were generated globally in the coffee production chain during the 2020/21 season. The current uses for these by-products are inadequate or contribute to environmental degradation. This work reports the screening of hydrophilic and hydrophobic solvents, including deep eutectic solvents (DES), for their ability to extract the valuable metabolites caffeine and chlorogenic acid (markers in commercial extraction) from four coffee-related by-products. Water was the best solvent for recovering caffeine and chlorogenic acid from defective green coffee beans, while all hydrophilic DES surpassed water in the extraction of chlorogenic acid from coffee pulp. For the two remaining by-products, at least one DES was as good or better at extracting the caffeine or chlorogenic acid compared to water. The array of hydrophobic solvents tested here showed different selectivities, allowing the annotation of 12 compounds that have not been previously reported in coffee by-products. These results demonstrate the ability to obtain a new and controllable range of extracts from coffee by-products using green and functional solvents.
Keywords: Biorefinery; Deep eutectic solvents; Low transition temperature mixtures; Natural designer solvents; Waste valorization